The Effect Of Compensation, Motivation And Work Environment On Job Satisfaction With Employee Performance As A Moderating Variable In Pt Putra Marindo Utama (Partial Least Square (Pls) - Structural Equation Modeling (Sem) - Abid muhtarom; Ike Susanti; Moh. Heru Budi Santoso; Nur Maziyyatul Muslimah (Enrichment : Journal of Management, 2022)
In a company, human resources are an important factor for the progress oflthe company, it can be said that a company will progress if it has skilled human resources in its field. This researcher has a novelty, namely the existence of additional variables studied. This type oflresearch is quantitative with a sample of 60 and the method nused to analyze is SEM (Structural Equation Modeling) with the Smart-PLS version 3.0 application. The test used is the Outer Model Test, Inner Model Test, Mediation Test, and Hypothesis Testing. based on the results of the Validity test, shows that the Loading Factor value > 0.7 and the AVE value > 0.5 are declared valid, in the reliability test the Composite Reliability and Cronbach's Alpha values > 0.7 are said to be reliable. It can be concluded that the Compensation Variable (X1) and Work Environment (X3) have a positive and significant effect on Job Satisfaction (Y). while motivation (X2) has no significant positive effect on job satisfaction (Y). From the Compensation Variable Mediation test (X1) on Job Satisfaction (Y) Mediated by Employee Performance (Z), it is said to be partial mediation. Motivation Variable (X2) Against Job Satisfaction (Y) Mediated Employee Performance (Z) is said to be Non- mediation. Work Environment Variable (X3) on Job Satisfaction (Y) Mediated by Employee Performance (Z) is said to be partial mediation.